Synthesis and physical-chemical properties of (3-benzyl-8-propylxanthin-7-yl)acetohydrazide derivatives and their evaluation for antimicrobial and diuretic activities - K. V. Aleksandrova; Ye. K. Mykhalchenko; O. S. Shkoda; D. A. Vasyliev (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2021)
One of the most important tasks of our indigenous pharmaceutical science is the necessity for new medicines because existing drugs are characterized by various side effects, resistance, high toxicity, and so on. New bioactive molecule synthesis utilizes substances of natural origin as well as chemically modified ones. Thus, the researcher’s attention is mainly focused on 3-,7-,8-substituted derivatives of the natural heterocyclic xanthine system, which possess a wide range of pharmacological action. Synthesis of a novel of (3-benzyl-8-propylxanthin-7-yl)acetohydrazides with antimicrobial and diuretic activities described in the paper.